Predictors of neuropathic dysesthetic pain occurrence and chronification in multiple sclerosis (2-year prospective study) - Delva, Mykhaylo; Skoryk, Kateryna; Delva, Iryna (Acta Biomedica Atenei Parmensis, 2023)
Background. Patients with multiple sclerosis (MS) are a high-risk group for neuropathic pain. Objective: to investigate predictors of neuropathic dysesthetic pain (NDP) occurrence and chronification in patients with MS during a 2-year observation period. Methods. After the exclusion criteria application and signing of informed consent, we recruited in the study 241 patients among which 23 patients prematurely stopped participating in the study. During the 2-year observation period, new NDP was diagnosed on the PainDETECT questionnaire (>18). Patients with newly diagnosed NDP were examined at baseline, in 1, 3, and 6 months depending on pain duration. The socio-demographic, neuropsychological, cognitive, sleep quality, and clinical characteristics of patients were evaluated at the beginning of the study and updated at baseline examination in cases of newly diagnosed NDP. Results. Over a 2-year observation period, NDP occurred in 34 patients (15.6%). Out of 34 cases of newly diagnosed NDP, in 20 cases (58.9%) pain became chronic (lasting longer than 3 months). In the Cox proportional hazards multifactorial model, progressive types of MS were an independent predictor of NDP occurrence (hazard ratio 2.60; 95% confidence interval, 1.30-5.18; p=0.01). In the multifactorial logistic regression analysis, subclinical depressive disorders (according to Hospital Anxiety and Depression Scale) were identified as an independent predictor of NDP chronification (odds ratio 7.14; 95% confidence interval, 1.12-45.59; p=0.04). Conclusions. In MS predictors of NDP occurrence are progressive types of MS, whereas predictors of NDP chronification are subclinical depressive disorders.